1990
DOI: 10.1007/bf00297227
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of histamine in flatworms

Abstract: Specific antibodies against histamine were used to demonstrate the occurrence and cellular distribution of histamine-like immunoreactivity in three species of flatworms (phylum Platyhelminthes). In the parasitic cestode Diphyllobothrium dendriticum, histamine-reactivity was found in neurons of the main nerve cords, and in cells lining the central and peripheral excretory ducts. In the free-living microturbellarian Microstomum lineare and in the planarian Polycelis nigra, histamine-immunoreactivity was restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

1991
1991
2008
2008

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 18 publications
1
16
0
2
Order By: Relevance
“…The existence of prolactin immunoreactive nerve cell bodies and fibres on the surface of the main excretory duct was observed in our previous study (Liu et al, 1996). 5-HT, peptide histidine isloeucine and histoaminergic immunoreactive cell bodies and fibres were also demonstrated in the wall of the ducts (Gustafsson et al, 1986and Wikgren et al, 1990). This finding and previous results suggest that neurosecretory cells are involved in the regulation of the excretory activity.…”
Section: Discussionsupporting
confidence: 58%
“…The existence of prolactin immunoreactive nerve cell bodies and fibres on the surface of the main excretory duct was observed in our previous study (Liu et al, 1996). 5-HT, peptide histidine isloeucine and histoaminergic immunoreactive cell bodies and fibres were also demonstrated in the wall of the ducts (Gustafsson et al, 1986and Wikgren et al, 1990). This finding and previous results suggest that neurosecretory cells are involved in the regulation of the excretory activity.…”
Section: Discussionsupporting
confidence: 58%
“…The data of histamine in the brain of other invertebrates are very limited. Wikgren et al (1990) demonstrated in different members of the Plathelminthes the occurrence of histamine in the nervous system and the distribution of histamine in the area of the excretory organs. Panula et al (1995) showed immunoreactivity in the region of the cerebral eye of Dugesia tigrina, but observed no histaminergic structures in the nervous system.…”
Section: Histaminementioning
confidence: 98%
“…Surprisingly little is known about the biology of HA in flatworms . In a parasitic flatworm Diphyllobothrium dendriticum numerous HA-ir nerve cells and fibres are found laterally to the main nerve cord (Wikgren et al, 1990) . In the microturbellarian Microstomum lineare two symmetrically placed pear-shaped HA-ir neurons are located on each side of the both excretory pores close to the presumptive photoreceptor cells (Palmberg et al, 1980 ;Wikgren et al, 1990) .…”
Section: Discussionmentioning
confidence: 99%